Editorial Vol.19(1-2) - Shrestha, Prithvi N; Dhakal, Khagendra Raj; Ojha, Laxmi Prasad; Rana, Lal Bahadur; Rawal, Hima (Journal of NELTA, 2015)
DOI: http://dx.doi.org/10.3126/nelta.v19i1-2.12669 Journal of NELTA, Vol 19 No. 1-2, December 2014: V-VII